EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERMEDIAKAN LEMBAR KERJA PESERTA DIDIK TERHADAP HASIL BELAJAR KIMIADAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SMA - SILABAN, RAMLAN; PANGGABEAN, FREDDY TUA MUSA; HUTAHAEAN, ESRIDA; HUTAPEA, FELIA MUTIARA; ALEXANDER, IRVING JOSAFAT (Jurnal Ilmu Pendidikan Indonesia, 2021)
The aim of this research is to know the effectivenessproblem based learning model (PBL) using student worksheet on learning outcomes and studentsâ€™critical thinking skills on the teaching Reaction Rate. The population in this research was grade 11th of SMA Negeri 6 Medan. Classes sample was taken by random sampling, and two classes were selected as a sample. Those two classes will be taught with Problem Based Learning model, the difference is the first class will be used students worksheets and the other class is not. The instrumentto conduct this researchwasÂ by test and non-test. Based on parametric statistical test, the result of pretest, postest, and studentsâ€™ critical thinking skills data from those two classes have a normal distribution and homogeny. Hypothesis was tested by using one tailed test with significant level ( ) =0,05. The data from hypothesis testing learning outcomes is tcal Â ttable (3,101 1,669), means Hois rejected and Ha is accepted. Hypothesis testing result on studentsâ€™ learning outcomes using student worksheets is higher than the non-using student worksheet. Critical thinking hypothesis test is tcal Â ttable (4,754 1,669), means Hois rejected and Ha is accepted. Hypothesis testing result oncritical thinking using student worksheet is higher than the non-using student worksheet. Contribution of studentsâ€™ critical thinking to the ups and downs of learning outcomes on the experiment class is 81,5%. Â